2005
DOI: 10.1002/anie.200461614
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Bonded Precursor Determines Particle Size Effects for Alkene Hydrogenation on Palladium

Abstract: Reactions of linear alkenes with metal surfaces have been previously studied on model catalyst systems with varying degrees of complexity, from single crystals to metal particles deposited on well-ordered oxide films. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Based on these studies, the majority of which were conducted with ethene, it has been suggested that alkene hydrogenation is structure insensitive. This means that the reaction only depends on the number of metal atoms on the surface and is inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
109
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 26 publications
4
109
0
1
Order By: Relevance
“…Thus, p-bonded pentene are not in direct contact with Pd and desorbs intact, and hydrogenation proceeds only via di-s-bonded species, which are favored on the terrace sites of large particles. Pentene hydrogenation is thus structuresensitive (121). PVP-stabilized Pt nanoparticles with the sizes between 1.7 and 3.6 nm also confirmed structure insensitivity of ethylene hydrogenation (47).…”
Section: Nanocatalysis With Controlled Shape and Sizementioning
confidence: 71%
See 1 more Smart Citation
“…Thus, p-bonded pentene are not in direct contact with Pd and desorbs intact, and hydrogenation proceeds only via di-s-bonded species, which are favored on the terrace sites of large particles. Pentene hydrogenation is thus structuresensitive (121). PVP-stabilized Pt nanoparticles with the sizes between 1.7 and 3.6 nm also confirmed structure insensitivity of ethylene hydrogenation (47).…”
Section: Nanocatalysis With Controlled Shape and Sizementioning
confidence: 71%
“…Using well-defined Pd/Al 2 O 3 model catalysts, where the particle size was varied in a controllable manner, the size effect in ethylene and trans-2-pentene hydrogenation was studied (121). Ethylene was adsorbed as a p-bonded species irrespectively of the surface composition explaining its hydrogenation structure insensitivity.…”
Section: Nanocatalysis With Controlled Shape and Sizementioning
confidence: 99%
“…Under both conditions, the ethylene hydrogenation reaction was found to be structure insensitive. In contrast, hydrogenation of 2-pentenes exhibited a significant particle size effect [19]. These studies have demonstrated that metal particles deposited on well-ordered oxide films are suitable model systems for studying mechanisms of the hydrogenation reactions o n supported metal particles.…”
mentioning
confidence: 90%
“…The low temperature (LT) state(s) can be attributed to the recombination of surface H species, which are more weakly bonded to the surface in the presence of sub-surface hydrogen. The sub-surface hydrogen is available for the reaction on the particles due to their limited size in contrast to Pd crystals where hydrogen may migrate into the bulk far away from the surface [16,17,19,22,23]. Upon heating of the Pd particles, surface H species are re-populated by the H atoms from the sub-surface region, finally leading to the situation where sub-surface hydrogen is depleted and the desorption becomes similar to the case of adsorption at 300 K.…”
mentioning
confidence: 99%
“…to size effects in hydrogenation reactions focus almost exclusively on supported (heterogeneous) Pd catalysts. [14][15][16] In addition to catalyst size, the preparation and structure of nanoparticles are also important factors that must be taken into account when comparing catalytic activity. This is because preparation methods, stabilizing ligands, and polydispersity can lead to activity changes that may mask true particle size effects.…”
mentioning
confidence: 99%